A case report of persistent Müllerian duct syndrome in a male patient with seminoma (Indian Journal of Case Reports, 2026)
Persistent Müllerian duct syndrome (PMDS) is a genetic disorder characterized by the persistence of Müllerian duct derivatives, including the uterus, fallopian tubes, and upper two-thirds of the vagina in a phenotypically and genotypically male patient. We report the case of a 44-year-old male with PMDS and an abdominal lump. On examination, he had a uterus and left testis on one side and pure seminoma arising in the right testis, confirmed on histopathological examination.